Recent allopolyploidization and transcriptomic asymmetry in the mangrove shrub Acanthus tetraploideus - Wuxia Guo; Achyut Kumar Banerjee; Hui Feng; Wei Lun Ng; Haidan Wu; Weixi Li; Yang Yuan; Yelin Huang (BMC Genomics)
Abstract Background Mangrove species are vital to the ecosystems of tropical and subtropical coastlines worldwide. Despite the underexplored role of polyploidization in these species, deciphering its impact on gene expression is essential for understanding the connection between polyploidization and species diversification. Our initial investigation, integrating multiple nuclear loci with morphological and cytological data, indicates that the tetraploid Acanthus tetraploideus likely originated from allopolyploidization events involving the diploid species A. ilicifolius and A. ebracteatus. Expanding on these insights, this study utilizes genome-wide evidence to confirm the divergence patterns among extant Acanthus mangrove diploids and to investigate the origin and transcriptome asymmetry of the tetraploid A. tetraploideus. Results Phylogenetic analysis and molecular dating revealed a closer evolutionary relationship between A. ebracteatus and A. volubilis than between A. ebracteatus and A. ilicifolius, diverged approximately 6.92 Mya and 9.59 Mya, respectively. Analysis of individual whole transcriptomes revealed that homeologous sequences in A. tetraploideus were preferentially clustered with A. ilicifolius and A. ebracteatus, rather than A. volubilis, in a roughly 1:1 ratio. The high similarity in nucleotide sequences and homologous polymorphisms between the tetraploid A. tetraploideus and its two parental diploids, A. ebracteatus and A. ilicifolius, supports the hypothesis of a recent allopolyploid origin for A. tetraploideus. Estimation of homeolog expression revealed a general attenuation of homeolog expression divergence in A. tetraploideus compared to the in silico parental mix, with 22.87% and 67.66% of genes exhibiting biased homeolog expression, respectively. Further investigation identified remarkable retention of parental expression dominance in the tetraploid, suggesting that parental genetic legacy substantially influences the reconfiguration of homeolog expression in the derived tetraploid. Meanwhile, the observation of numerous novel expression patterns between the two homeolog sets suggests that the transcriptome shock (i.e., the transcriptomic changes induced by interspecific hybridization) associated with allopolyploidization and subsequent post-polyploid evolutionary processes also significantly impact transcriptome asymmetry in A. tetraploideus. While no strong evidence directly links transcriptomic changes to specific adaptive traits, the patterns in unbiased and novelly biased genes in A. tetraploideus suggest adaptations to stable polyploidy. Unbiased genes involved in fundamental cellular processes and novelly biased genes related to chromosome dynamics and cell cycle regulation may stabilize polyploid genomes, supporting the species’ establishment and long-term success. These findings underscore the role of transcriptomic stability in polyploid adaptation. Conclusions Our study sheds light on the evolutionary origins and the intricate transcriptional reconfiguration of the tetraploid A. tetraploideus. These insights significantly enhance our comprehension of the pivotal role that polyploidization plays in speciation and adaptative evolution of mangrove species.